THE DEVELOPMENT OF WEB-BASED CREDIT TRANSFER APPLICATIONS IN THE FACULTY OF SCIENCE AND TECHNOLOGY UNIVERSITAS TERBUKA (A CASE STUDY IN THE INFORMATION SYSTEM PROGRAM) - Nurdiana, Dian; Susilo, Adhi; Aprijani, Dwi Astuti; Suryadi, Andri (International Journal of Global Operations Research, 2021)
The implementation of credit transfer at Universitas Terbuka refers to the Rector's Regulation Number 119, 2018. This credit transfer could only be carried out once when students registered themselves at very first time. Recognition of credit transfer is accepted whn accomplishment of courses have been obtained from their previous universities. Through the provision of credit transfer recognition services, students are expected to be able to finish their study faster. Students can apply for credit transfer through the Faculty which would then be proceed by Study Program. Students are required to collect documents such as diplomas, transcripts, descriptions of courses at their previous university, and the submissions for courses intended to be transferred for credit. The documents which are in form of print out would later be processed in their respective Study Programs. During the process, the Study Program compiled the documents manually by recording and determining the courses approved for credit transfer. However, the study Program hasnâ€™t used a special application. Due to this limitation, several problems occurred in the process, such as the absence of filing the credit transfer application documents, the ineffectiveness of storing the credit transfer master block in the Study Program, and the large number of credit transfer applications. These problems often result in delays in the credit transfer process, thus disrupting academic services for students. Therefore, it is necessary to develop a credit transfer application that can assist in the implementation of credit transfer in the Faculty of Science and Technology. The methodology used to develop this credit transfer application is the waterfall model. For design modeling using UML (Unified Modeling Language), while software testing uses Black Box Testing and usability and acceptance tests applied the PSSUQ (Post-Study System Usability Questionnaire) method. From the results of the tests, it showed that Black Box Testing got test results of 100%, while the usability and acceptance tests using the PSSUQ method got 68% of respondents. The conclusion of this study showed that the application is ready to use and the users Agree/Good/Like on the development of a web-based credit transfer application at the Faculty of Science and Technology of the Universitas Terbuka (case study of Information Systems Study Program).Â Kata kunci: Credit transfer, Web, Waterfall, , Black Box Testing, PSSUQ.